The student legal awareness against the hazards of smoking for health in school - Yasnita; Dwi Afrimetty Timoera; Asep Rudi Casmana; Iqbal Syafrudin (Jurnal Ilmiah Mimbar Demokrasi, 2021)
ABSTRACTThe purpose of this study was to find out about (1) The level of legal awareness regarding the dangers of smoking for the health of junior and senior high school students (2) Strategies that need to be done to increase legal awareness regarding the dangers of smoking for the health of junior and senior high school students in the capital city of Jakarta. This research is a research using descriptive qualitative. The method of collecting data is through online interviews. Respondents in this study were 13 civic education teachers at the junior and senior high school levels and 10 junior high school students. The data analysis technique uses data reduction, data display and data verification. The results showed (1) The level of legal awareness of students against the dangers of smoking was very good, this can be seen from the majority of students obeying the smoking prohibition rules in schools. Even so, there are still some unscrupulous students who are caught smoking and bringing vapes (e-cigarettes) to school. (2) The strategy that has been carried out by teachers in schools to increase the legal awareness of students regarding the dangers of smoking for the health of junior high and high school students in the capital city of Jakarta is by increasing legal knowledge and awareness of students through repressive, preventive and maximally repressive through learning civic education. ABSTRAKTujuan penelitian ini adalah untuk mengetahui tentang (1) Tingkat kesadaran hukum terkait bahaya merokok bagi kesehatan siswa-siswi SMP dan SMA di DKI Jakarta dan Banten; (2) Strategi yang perlu dilakukan untuk meningkatkan kesadaran hukum terkait bahaya merokok bagi kesehatan siswa-siswi SMP dan SMA di DKI Jakarta dan Banten. Penelitian ini adalah penelitian dengan menggunakan kualitatif deskriptif. Metode pengumpulan data melalui wawancara dan analisis datanya menggunakan reduksi data, display data dan verifikasi data. Hasil penelitian menunjukkan (1) Tingkat kesadaran hukum berlalu lintas peserta didik di Kota Makassar tergolong cukup baik, hal ini terlihat dari mayoritas siswa-siswi mematuhi aturan larangan merokok di sekolah. Meskipun demikian, masih ada beberapa oknum siswa yang ketahuan merokok dan membawa vape (rokok elektrik) ke sekolah. (2) Strategi yang telah dilakukan oleh para guru di sekolah untuk meningkatkan kesadaran hukum peserta didik terkait bahaya merokok bagi kesehatan siswa-siswi SMP dan SMA di DKI Jakarta dan Banten adalah dengan cara meningkatkan pengetahuan dan kesadaran hukum para siswa-siswi melalui upaya preemtif, preventif dan represif secara maksimal.